ACTIVITY OF NITRIFYING BACTERIA (AMMONIA OXIDIZER AND NITRITE OXIDIZER) IN BRACKISHWATER PONDS (TAMBAK) IN BENGKALIS ISLAND, RIAU PROVINCE - Feliatra . (JOURNAL OF COASTAL DEVELOPMENT, 2001)
A research study was carried out from April to July 1999, on brackishwater ponds in Bengkalis Island, Riau Province, Indonesia.  Observations and samplings were taken from three stations.  Six nitrifying bacteria were isolated from ammonium oxidizer and four from nitrite oxidizer. The nitrifying bacteria activity varied from 0,024 to 0,092 ppm/day for ammonia oxidizer, and from 0,032 to 0,052 ppm/day for nitrite oxidizer. These nitrifying bacteria can reduce the ammonia concentration; in the brackish water ponds. In the absence of nitrifying bacteria, the ammonia concentration was so toxic, it was killed the shrimp at 31 days after sampling